2009
DOI: 10.1002/lary.5541121410
|View full text |Cite
|
Sign up to set email alerts
|

Power-Assisted Partial Adenoidectomy

Abstract: We and other authors have found power-assisted partial adenoidectomy to provide a faster, more precise operation than curette techniques, with benefits for both patient and surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 5 publications
1
32
1
Order By: Relevance
“…On an average, microdebrider saved 4 min 46 s which is highly significant while the amount of blood loss in both the groups was not of significant difference. A similar prospective study of 140 cases by Rodigruez et al [20] has evaluated various parameters like intra-operative time and amount of bleeding showing significant reduction in the surgical time in group B as compared to group A. A prospective study by Somani et al [12] (of 44 children) and a retrospective study by Costatini et al [21] (of 201 children) reported an operating time (with microdebrider assisted adenoidectomy) as 12.5 min each and the average blood loss of 30 and 28 ml respectively.…”
Section: Number Of Cases Completeness Of Removal On Nasal Endoscopymentioning
confidence: 78%
“…On an average, microdebrider saved 4 min 46 s which is highly significant while the amount of blood loss in both the groups was not of significant difference. A similar prospective study of 140 cases by Rodigruez et al [20] has evaluated various parameters like intra-operative time and amount of bleeding showing significant reduction in the surgical time in group B as compared to group A. A prospective study by Somani et al [12] (of 44 children) and a retrospective study by Costatini et al [21] (of 201 children) reported an operating time (with microdebrider assisted adenoidectomy) as 12.5 min each and the average blood loss of 30 and 28 ml respectively.…”
Section: Number Of Cases Completeness Of Removal On Nasal Endoscopymentioning
confidence: 78%
“…This analysis considered 12 articles. Among these, the techniques can be schematically divided in non-endoscopic, usually performed with a laryngeal or a dental mirror [1][2][3][4][5]21], and endoscopic-assisted [6,11,[25][26][27]. The endoscopic control can be obtained either trans-nasally or trans-orally, as well as the microderbider can be inserted in the nasal cavity (straight blades) or maneuvered through the oral cavity (curved blades).…”
Section: Materials Methods and Resultsmentioning
confidence: 99%
“…The classic surgical technique performed with an adenoid curette or an adenotome has recently evolved by the introduction of the endoscopic sinus surgery instrumentation, with an improved patients' outcome and a better satisfaction of the surgeon [1][2][3][4][5][6]. The standard adenoidectomy technique is performed with an adenoid curette or an adenotome, under general anesthesia via oro-tracheal intubation [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both the hand piece and the endoscope can be introduced through the oral cavity if the nasal fossa is too narrow, in younger children. One of the major advantages of using the microdebrider is having the option to remove adenoid tissue only partially (Rodriguez et al, 2002;Koltai et al, 2002), as in cases of insufficient velopharyngeal valve, in cases of repaired cleft palate, and those with submucous cleft palate.…”
Section: Endoscopic Micro-debrider-aided Adenoidectomymentioning
confidence: 99%